Укротитель сиреневых бегемотов - Георгиев Сергей Георгиевич (Школа прикола, 2007)
Экземпляры: ф. 15 (20230127) / Инвентарный номер: 64780 / Цена: 50.00 / Авт.знак: Г 36 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6